Molecular Analysis of pSK1 par: A Novel Plasmid Partitioning System Encoded by Staphylococcal Multiresistance Plasmids. Issue 19 (15th October 2022) - Chan, Helena Y.; Jensen, Slade O.; LeBard, Rebecca J.; Figgett, William A.; Lai, Evelyn; Simpson, Alice E.; Brzoska, Anthony J.; Davies, Danielle S.; Connolly, Angela M.; Cordwell, Stuart J.; Travis, Brady A.; Salinas, Raul; et al.
Graphical abstract: Highlights: The prototypical multiresistance plasmid pSK1 encodes a single par protein, pSK1 Par. Unlike typical par systems, requiring 2 proteins, pSK1 Par alone drives pSK1 partition. pSK1 Par-DNA structure reveals distinct CBP fold and centromere binding mechanism. Biochemical analyses show pSK1 Par forms extended coiled-coiled oligomer. In vivo data show pSK1 Par enhances plasmid separation of plasmids from clusters. Abstract: The segregation of prokaryotic plasmids typically requires a centromere-like site and two proteins, a centromere-binding protein (CBP) and an NTPase. By contrast, a single 245 residue Par protein mediates partition of the prototypical staphylococcal multiresistance plasmid pSK1 in the absence of an identifiable NTPase component. To gain insight into centromere binding by pSK1 Par and its segregation function we performed structural, biochemical and in vivo studies. Here we show that pSK1 Par binds a centromere consisting of seven repeat elements. We demonstrate this Par-centromere interaction also mediates Par autoregulation. To elucidate the Par centromere binding mechanism, we obtained a structure of the Par N-terminal DNA-binding domain bound to centromere DNA to 2.25 Å. The pSK1 Par structure, which harbors a winged-helix-turn-helix (wHTH), is distinct from other plasmid CBP structures but shows homology to the B. subtilis chromosome segregation protein, RacA. Biochemical studies suggest the region C-terminal to the Par wHTH forms coiled coils and mediates oligomerization. Fluorescence microscopy analyses show that pSK1 Par enhances the separation of plasmids from clusters, driving effective segregation upon cell division. Combined the data provide insight into the molecular properties of a single protein partition system.